TRENDS IN ISLAMIC EDUCATION RESEARCH: A BIBLIOMETRIC PERSPECTIVE ON THE GLOBAL LITERATURE 2014 -2024 - Nurhikmah, Cece (Journal of Innovation Research and Knowledge, 2025)
Study This aiming For identify global trends in study Islamic education during period 2014–2024, with focus on pattern publication, theme main, and collaboration writer. Using approach quantitative based on analysis bibliometrics, data obtained from the Scopus database via keyword search​ such as "Islamic Education" and "Islamic Studies AND Education." With PRISMA method, 291 articles met the criteria criteria inclusion analyzed use device soft VOSviewer And Biblioshiny For map trend publication, distribution geographic, collaboration between author, and keyword theme.​ Results show improvement significant in publication with level growth annual average of 10.79 %, with theme main such as "Islamic Education," and "Education" which dominate. However, only 7.216% of the documents involve collaboration international, reflecting domination study local. New study This located on visualization of co-occurrence keywords and thematic mapping that reveals potential development theme like gender in Islamic education, nationalism, and diaspora. Study This give outlook for academics For explore theme new And increase collaboration cross country, and help identify gap study For development more Continue. Results study expected enrich related global literature Islamic education.